Agriculture urbaine et habitat humain - Louiza Boukharaeva; Marcel Marloie (Revue d'ethnoécologie)
In Chapter 9, « The Urban Challenge », the Brundtland Report recommended developing urban agriculture. The research that ensued has focused on its contribution to food production, the struggle against poverty, improving the quality of soil, air and water. But it still seems to be a marginal activity for a small fraction of the urban population with medium or low income. Experiences in Russia and other European countries show a phenomenon of greater magnitude which can interest most city dwellers. Indeed, it offers the possibility of supplementing an urban home with a plot in which one can combine food production and recreation (rest, health improvement, freedom of activity, strengthening of family ties), according to their needs, their desires, and their constraints. With a surface varying between 300 and 1000 m², the individual plots of land in the allotment gardens, allotment vegetable gardens and dacha allotments concern about a quarter of the urban population of Russia, and less in other countries. The right to build a small house in which to stay for weekends and holidays expands their multifunctionality. This extra-professional and non-market activity was a social conquest within the Soviet regime. It provides an alternative to the suburban model which pollutes and destroys soils. By helping people overcome stress and contributing significantly to avoid the risks of famine, it was a shock absorber of the systemic crisis of the 1990s. Contrary to the prevailing view since 1929 that individual gardening carries a « petty bourgeois » spirit, it actually allows to invent lifestyles more compatible with the existential needs of individuals. This family urban agriculture is a way to build a more autonomous, more social and more ecological urban society. It is a necessity for the resilience of individuals, families and society.